Modeling the MSME Sector on Labor Absorption in Aceh - Adnan, Muhammad; Meutia, Rachmi; Marwiyati, Marwiyati; Dinillah, T Hafizhly (Jurnal Manajemen, 2023)
The existence of MSMEs in Aceh reduces unemployment by employing the working-age population. In addition, turnover for MSMEs is essential because an increase in turnover will impact the expansion of business units in the sector and increase the need for labor. This study aimed to test and analyze the effect of the number of business units and turnover on employment in the MSME sector in Aceh. This research used an associative quantitative approach. The panel data was used in this study including 23 districts/cities from 2018-2020 period. Panel data regression uses three estimation methods: the Common Effect model, the Fixed Effect model, and the Random Effect model. The Chow, Hausman, and Lagrange Multiplier tests are used to select the best estimation model. The Random Effect Model is the best estimation model in this study. Based on the estimation results, the number of business units and turnover positively and significantly affect employment in the MSME sector in Aceh. The variable number of business units has the most influence on work in the MSME sector in Aceh. The research conducted in Aceh province uses panel data in 23 districts/cities for the period 2018-2020 so that the results of this study can illustrate the existence of MSMEs in absorbing labor in Aceh Province.